A comment on "temporal variation in survival and recovery rates of lesser scaup". Issue 7 (20th April 2017) - Lindberg, Mark S.; Boomer, G. Scott; Schmutz, Joel A.; Walker, Johann A.
ABSTRACT: Concerns about declines in the abundance of lesser scaup ( Aythya affinis ) have promoted a number of analyses to understand reasons for this decline. Unfortunately, most of these analyses, including that of Arnold et al. (2016 Journal of Wildlife Management 80: 850–861), are based on observational studies leading to weak inference. Although we commend the efforts of Arnold et al. (2016 Journal of Wildlife Management 80: 850–861), we think their conclusions are over‐stated given their retrospective analysis. Further, we note a number of inconsistencies in their reasoning and offer alternative conclusions that can be drawn from their analysis. Given the uncertainty still surrounding management of lesser scaup, we do not believe it is prudent to abandon or greatly modify adaptive management approaches designed specifically to make optimal decisions in the face of uncertainty. The current learning‐based and recursive approach to management appears to be providing adequate guidance for harvest without punctuated changes to harvest levels, as Arnold et al. (2016 Journal of Wildlife Management 80: 850–861) recommend. © 2017 The Wildlife Society. Abstract : We argue that the uncertainty associated with harvest dynamics of lesser scaup and the sensitivity of scaup to changes in survival warrant an adaptive approach to harvest management that includes conservative assumptions.